Honda and It’s Dominance in Indonesia: The Unforgettable Key to Customer Satisfaction - Eko Oby Purwanto; Abdullah, Muhammad; Ati Chandrasari; Ratna Puspita (SEAN Institute, 2024)
This study aims to explore the relationship between product quality, brand image, purchasing decisions, and customer satisfaction within the context of Honda motorcycle brand. A total of 96 respondents who owned Honda motorcycles in Jakarta participated in the research, employing a non-probability sampling technique, specifically purposive sampling. The research utilized descriptive and inferential analyses, facilitated by the SmartPLS 4.0.9.9 application. The findings revealed several significant relationships: Firstly, both product quality and brand image positively and significantly influence purchasing decisions. Secondly, product quality and brand image also individually contribute positively and significantly to customer satisfaction. Thirdly, purchasing decisions positively and significantly impact customer satisfaction. Furthermore, mediation analysis indicated that product quality and brand image, mediated through purchasing decisions, positively and significantly influence customer satisfaction. This study underscores the critical role of product quality and brand image in shaping purchasing decisions and subsequent customer satisfaction, particularly within the Honda motorcycle brand context. These findings provide valuable insights for marketers and managers aiming to enhance customer satisfaction and brand loyalty.